Perspectivas e riscos de lesões na retomada de atividades esportivas de alto rendimento após isolamento social devido à pandemia de COVID-19 - de Paula Atti, G.; Pereira da Silva, A.; Lazzareschi, L.; Filoni, E. (Brazilian Journal of Health Review, 2020)
The objective of this narrative review was to discuss whether distance training was able to maintain physiological, cardiovascular and muscular conditions to safe return to elite athletes to their activities, and what risks of injuries they will be submitted to. Considering this unprecedent situation, and the lack of studies that address the possible risks of injury associated with returning to high-performance sports after social isolation we aim to collect such data in the present article. Since December 2019, the world has been affected by a pandemic caused by the new coronavirus. Similar situation had only occurred more a hundred years ago, when the Spanish flu affected Europe around 1918. Although most athletes are likely to experience only mild symptoms as a result of coronavirus infection, preventive strategies are necessary